Genre Analysis of Mr. Hundert and Sedgwick Bell’s Dialogues in The Emperor’s Club - Rahman, Erwan; Norahmi, Maida; Emeral; Khodijah, Fadila Umi; Munawarah, Siti (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to analyze the conversations between Mr. Hundert and Sedgewick Bell in The Emperor’s Club through a qualitative case study with genre-based discourse analysis, grounded in Halliday’s Systemic Functional Linguistics. By employing techniques such as framing, foregrounding, backgrounding, and presupposition, the study reveals how linguistic choices reinforce ideological conflicts between moral idealism and pragmatic ambition. The findings suggest that these ideological tensions reflect broader dilemmas in character education, especially relevant to Indonesia’s Kurikulum Merdeka and the Pancasila Student Profile. The study has implications for literature-based pedagogy and ethical development in classroom settings.